Concurrent bilateral patellar tendon ultrasonic debridement in a collegiate athlete - a case report - Kruse, R. C.; Krill, M.; Solsrud, E. (Current Sports Medicine Reports, 2022)
Concurrent bilateral patellar tendon ultrasonic tenotomy and debridement can be performed safely and successfully in high-level athletes.